2013
DOI: 10.2106/jbjs.l.00989
|View full text |Cite
|
Sign up to set email alerts
|

EOS Low-Dose Radiography

Abstract: This study assesses the reliability and accuracy of a diagnostic test used for clinical decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(43 citation statements)
references
References 22 publications
2
40
0
Order By: Relevance
“…The results are comparable with the length measurements performed by Escott et al [13], who compared four different measurement techniques (standard radiographs, CT scans, EOS-slow, and EOS-fast) for leg length measurements with respect to a phantom of known length. EOS-slow measurements performed most accurately with an average 0.5% underestimation of the phantom length.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The results are comparable with the length measurements performed by Escott et al [13], who compared four different measurement techniques (standard radiographs, CT scans, EOS-slow, and EOS-fast) for leg length measurements with respect to a phantom of known length. EOS-slow measurements performed most accurately with an average 0.5% underestimation of the phantom length.…”
Section: Discussionsupporting
confidence: 86%
“…Most studies use conventional means such as radiographs or MRI [13, 3335]. Terjesen et al, however, showed that 95% of the ultrasound leg length measurements on 45 subjects were within 7 mm of the radiographic measurements [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 ). 10 11) The EOS image is reconstructed as if it was acquired in the patient's reference plane and limits the distortion to the patient's thickness instead of the whole distance between the source and the detector. 7) In particular, EOS is useful when measuring the sagittal alignment on spine and pelvis images by drawing a line along the whole vertebra or calibrating it to the center of both hip joints.…”
mentioning
confidence: 99%
“…This upright standing position allows for a more accurate recording of the patient's functional weight-bearing leg alignment [10]. Furthermore, EOS images provide information on the whole leg, not just a pelvic overview, and the patient is exposed to a lower radiation dose than with a conventional X-ray [11,12]. Hence, it is possible to extract clinical leg parameters that have not been previously studied in relation to gait.…”
Section: Introductionmentioning
confidence: 99%